«A quale dito di Stockhausen sei appeso?» - Cavallotti, Pietro (Mimesis Journal, 2020)
In the late 60’s and early 70’s the topic of free improvisation has played an important role at the Summer Courses in Darmstadt. Particularly significant were the seminars of Vinko Globokar (with the group New Phonic Art) in 1970, especially focused on the importance of the performative moment, on the question of authorship in the case of collective performances, as well as on the absolute necessity of internal democratic dynamics within the improvisation group. The emphasis accorded to this latter aspect can be explained by the particular conditions in which the question of improvisation was introduced into the Darmstadt debate: the dispute between Karlheinz Stockhausen, Globokar and many other participants of the courses during the last session of Stockhausen’s seminar about Aus den sieben Tagen at the Summer Course of 1969. The whole debate (a very passionate dispute lasting about two hours) was about the “dictatorial” role of Stockhausen during the performances of his “intuitive music”, in which Globokar’s Group was actively involved as well. The essay aims to reconstruct and contextualise the main phases of this debate, in which two opposite visions of collective musical improvisation collide.